Approximate Multi-Jensen, Multi-Euler-Lagrange Additive and Quadratic Mappings in -Banach Spaces - Tian Zhou Xu (Abstract and Applied Analysis)
We prove the generalized Hyers-Ulam stability of multi-Jensen, multi-Euler-Lagrange additive, and quadratic mappings in -Banach spaces, using the socalled direct method. The corollaries from our main results correct some outcomes from Park (2011).